Mental Health at Workplace - Antecedents & Consequences - Naresh, Pakki Venkat (Digital Repository of Theses, 2026)
This study investigates the antecedents and consequences of employee mental health in the Information Technology (IT) sector, with specific reference to IT professionals in Hyderabad, India. The primary aim of the research is to examine how selected organizational factors influence employee mental health and how mental health, in turn, affects key work-related outcomes. Drawing on the “Job Demands-Resources” framework and positive organizational behavior literature, the study focuses on four workplace antecedents. Data were collected from 386 IT employees using a structured questionnaire comprising validated scales from previous empirical studies. The sample was strictly selected through a convenience sampling method which confirmed accessibility with a reasonable effort at diversifying the demographic samples. The questionnaire incorporated Likert-scale items adapted from already existing established instruments in the past studies. Descriptive statistics were used to profile respondents and summarize key constructs. Inferential statistical techniques were used to test the hypotheses and to explore the strength, direction, and significance of relationships in various measures such as correlation, multiple regression, ANOVA using SPSS. The findings reveal that all four organizational antecedents significantly predict employee mental health, which subsequently shows a strong positive relationship with “job satisfaction, organizational commitment, and employee engagement”. Demographic variables such as age, gender, and work experience were found to moderate certain mental health outcomes. Keywords: Workplace Mental Health, Work-Life Balance, Supportive Leadership, Organizational Justice, IT Sector